Product distribution and interactive mechanism during co-pyrolysis of a subbituminous coal and its direct liquefaction residue. (1st July 2017) - Li, Xiao-hong; Li, Li-li; Li, Bao-fu; Feng, Jie; Li, Wen-ying
Graphical abstract: Highlights: Experiments verify the interaction between coal and DCLR during co-pyrolysis. The interaction comes from the redistribution of free radicals between coal and DCLR during co-pyrolysis. More large free radicals from DCLR are stabilized by free radicals from coal in co-pyrolysis. Abstract: Compared with individual pyrolysis of Shendong coal or the direct coal liquefaction residue, co-pyrolysis has an improved tar yield. However, the synergistic mechanism in the integrated process is still controversial. In order to explore the interactive effect in co-pyrolysis of coal and the direct coal liquefaction residue, elemental analysis, gas chromatography, Fourier – transform infrared spectrometer, thermogravimetric simulation distillation, nuclear magnetic resonance and gas chromatograph – mass spectrometer were employed to analyze the structure and chemical composition of products (gas, semi-coke, and tar) obtained in co-pyrolysis at 600 °C. The results show that the actual product yields are different from the calculated values and elemental redistribution occurs in co-pyrolysis. Instruments characterization suggests an increased loss of aromatic hydrogen and carbon in co-pyrolysis, in comparison with individual pyrolysis. The increasing tar is mainly composed of heavy components with boiling points higher than 400 °C. Co-pyrolysis favors the minimization of the dealkylation of phenolic species. Furthermore, the synergistic mechanism analysis using two-stage reactor indicates that the increase in tar yield should be attributed to the change in the free radical reaction during the pyrolysis of Shendong coal and the direct coal liquefaction residue. In co-pyrolysis, more radicals generated from coal pyrolysis are used to stabilize the radicals generated from the pyrolysis of tetrahydrofuran soluble fraction of the direct coal liquefaction residue.